Defining the pediatric response to SARS-CoV-2 variants - Ho, Reanne M.; Bowen, Asha C.; Blyth, Christopher C.; Imrie, Allison; Kollmann, Tobias R.; Stick, Stephen M.; Kicic, Anthony (Frontiers in Immunology, 2023)
The global population has been severely affected by the coronavirus disease 2019 (COVID-19) pandemic, however, with older age identified as a risk factor, children have been underprioritized. This article discusses the factors contributing to the less severe response observed in children following infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), including, differing viral entry receptor expression and immune responses. It also discusses how emerging and future variants could present a higher risk to children, including those with underlying comorbidities in developing severe disease. Furthermore, this perspective discusses the differential inflammatory markers between critical and non-critical cases, as well as discussing the types of variants that may be more pathogenic to children. Importantly, this article highlights where more research is urgently required, in order to protect the most vulnerable of our children.